(RETRACTED) The Reconstruction of Women's Position and Role through Irigaray's Ethics of Sexual Differences in the Culture of Manggarai, Flores, East Nusa Tenggara - Candra, Priskardus Hermanto; Zunaidah, Asih; Gasa, Frederik Masri (Sawwa: Jurnal Studi Gender, 2020)
Reason for Retraction (March 26th, 2021):This paper is retracted by the editors due to publication ethics misconducted by authors (simultaneous publication in another journal).Â